Developing Employee Career Adaptability: Individual-Organizational Perspectives - Anggraeni, Ade Irma (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
Research in the field of employment relationships also emphasises that HR management should not stop at adopting technical HR management practices without considering the dynamics of employee aspirations and expectations. The characteristics of today's workforce are unique in that they combine a high career orientation with the need to work in a conducive work environment. Employees are no longer focused on long-term job security, but on the organisation's ability to provide career development for employees so that employee competencies and skills can always keep up with the demands of the labour market. This study aims to analyse individual and organisational factors that influence the development of career resilience.